Stock market liberalization and earnings management: Evidence from a quasi‐natural experiment in China - Gao, Kaijuan; Pittman, Jeffrey; Wang, Xiongyuan; Wang, Zi‐Tian (Contemporary Accounting Research, 2023)
Abstract Exploiting a quasi‐natural experiment in China in which some firms become investible to foreign investors across different times (i.e., pilot firms), we explore the role that stock market liberalization plays in shaping firms' earnings management activities. In one direction, the national‐level liberalization reform may elicit public attention from various stakeholders, piling pressure on managers to refrain from distorting their firms' earnings. In the other direction, the various restrictions that the government imposes on foreign investors cast doubt on whether China's capital control reform will materially affect pilot firms' incentives and scope to manipulate their earnings. To gauge which force is more dominant, we rely on a staggered difference‐in‐differences research design and find that pilot firms significantly reduce the magnitude of their discretionary accruals and the incidence of financial reporting irregularities from the pre‐ to the post‐liberalization period, compared to non‐pilot firms during the same time frame. Additional analysis implies that externalities in the form of stricter external monitoring from the media, institutional investors, and auditors is the major mechanism that helps market liberalization curb firms' earnings management. Our research provides insight on the importance of financial global integration to firms' earnings management practices.